FRI0343 Evaluation of the Impact of Current Treatment on Serum Urate Profile, Gout Flares and Tophi in Patients with Gout in France, Germany, United Kingdom and the United States. (9th June 2015) - Nuevo, J.; Nyberg, F.; Horne, L.; Morlock, R.; Storgard, C.; Aiyer, L.; Hines, D.M.; Ansolabehere, X.; Chevalier, P.
Abstract : Background: Gout affects 1–4% of the population in developed Western countries. The goal of gout treatment is lowering serum uric acid (sUA) levels to treat and prevent urate crystal deposition, thereby improving signs and symptoms of gout, e.g., acute flares and tophus formation. Objectives: Describe impact of current urate-lowering treatment (ULT) on sUA, gout flares and tophi in patients with established gout in France (Fr), Germany (DE), the United Kingdom (UK) and the United States (US). Methods: A retrospective database analysis was conducted using Disease Analyzer database (Fr, DE), IMS' PharMetrics Plus™ database linked with outpatient laboratory results (US), and Clinical Practice Research Datalink-Hospital Episode Statistics (UK) from Jan 1, 2009 to Dec 31, 2011. Patients were required to have evidence of "prevalent established gout" (ie, treated with or eligible for ULT based on ACR guidelines) between Jan 1, 2009 and Dec 31, 2009; be age ≥18 on index date (Jan 1, 2010); and have ≥1 documented visit prior to Jan 1, 2009 and ≥1 documented visit for gout after Jan 1, 2010. Follow-up extended from Jan 1, 2010 to Dec 31, 2011 (all dates +1 yr for France). Univariate descriptive statistics were conducted to describe elevated sUA occurrence (≥6 mg/dL), gout flares, and tophi by ULT (allopurinol [ALLO] and febuxostat [FBX]). Results: A total of 22126 (Fr), 58672 (DE), 36188 (UK) and 169085 (US) patients met selection criteria. ALLO:FBX populations were 13995:1, 785 (Fr), 36251:429 (DE), 21409:101 (UK), and 82415:3610 (US). Mean (SD) age 68.0 (12.3), 69.2 (11.0), 64.6 (12.3) and 54.5 (9.6) years, respectively. Most patients were male (Fr: 74.9%; DE: 70.3%; UK: 85.6%; US: 89.2%). Availability of sUA results varied by country, but was low, ranging from 2.4% (US) to 41.0% (DE). For sUA, study population included only patients with ≥1 sUA measure. Observed incidence rates of elevated sUA episodes (8 to 58 per 100 patient yrs), 1st gout flare during follow-up (1.1 to 60 per 100 patient yrs), and percentage of patients with reported tophus (up to 2.3%), by country and stratified by ULT, are provided (Figure ). Conclusions: Current ULT (eg, ALLO, FBX) often do not achieve recommended sUA goals and gout-related outcomes, with many patients experiencing elevated sUA levels. In this multinational database analysis of ULT-treated patients, high number of elevated sUA episodes, evidence of continued flares, and percentage of patients with reported tophus over the observation period present continued need for improvement in gout treatment. Notably, sUA testing rates were low (<15% in 3 of 4 countries), denoting a critical gap in gout management. More diligent sUA testing, as well as newer treatment approaches, may provide the ability to further improve outcomes and gout control for some patients. References: Soriano LC, Rothenbacher D, Choi HK, Rodriguez LAG. Arthritis Res Ther. 2011;13:R39-47. Zhang W, Doherty M, Pascual E et al. Ann Rheum Dis 2006;654:1301-1311. Roddy E, Doherty M. Arthritis Res Ther. 2010;12:223-233. Acknowledgements: This study was funded by AstraZeneca. Editorial support was provided by PAREXEL and funded by AstraZeneca. Disclosure of Interest: J. Nuevo Employee of: AstraZeneca, F. Nyberg Employee of: AstraZeneca, L. Horne: None declared, R. Morlock Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group, C. Storgard Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group, L. Aiyer Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group, D. Hines Employee of: IMS Health, X. Ansolabehere Employee of: IMS Health, P. Chevalier Employee of: IMS Health